TINJAUAN YURIDIS TERHADAP KASUS BULLYING VERBAL DI LINGKUNGAN SEKOLAH BERDASARKAN UU NO. 35 TAHUN 2014 - Emirenciana Aek Bria; Merli serlianti Beis; Christy Revalina Teuf; Maria Muliani Mali; Nadia N.S.Y Lodo; Fadil Mas'ud (STKIP Subang, 2026)
Verbal bullying is a form of mental violence prohibited by Article 76C of Law No. 35 of 2014, with a maximum prison sentence of 3 years and 6 months for perpetrators. Based on the mandate of Article 54, schools must ensure a violence-free educational environment for all students. Given that perpetrators are often children, case resolution must prioritize diversion mechanisms and restorative justice, as stipulated in Law No. 11 of 2012 (SPPA), to protect children's rights and futures. Overall, firm and educational law enforcement are crucial for creating safe and humane schools.